Studies on suppression of bacterial leaf blight by rice endophytic bacteria under field condition - Kavitha, K; Nagamani, P; Madhu Sudhan, P; Viswanath, K; Reddy, NP Eswara (ORYZA-An International Journal of Rice, 2020)
A total of 45 endophytic bacterial isolates were isolated from the healthy rice cultivars viz; MTU 1010, BPT 5204 and NLR 34449 cultivated in Nellore and Chittoor districts of Andhra Pradesh. All the isolated endophytic bacterial isolates were evaluated for their antagonistic effect against bacterial leaf blight (BLB) pathogen Xanthomonas oryzae pv. oryzae by agar well diffusion method. The diameter of inhibition zone formation ranged from 0 mm to 16.8 mm. Among 45 isolates, EMP-5 and EBK-3 isolates showed highest antagonistic effect with inhibition zone of 16.8 mm and 16.6 mm, respectively. Isolate EMP 5 was used for the management of BLB under field condition. Among all the treatments, treatment T5 (i.e., seed treatment with EMP-5 @ 109 cells ml-1 + foliar application of EMP-5 @109 cells ml-1) exhibited highest reduction in disease index (4.92 %), increased plant growth promoting ability with plant height of 80.8 cm, increase in the no. of effective tillers (97.4 %), grain yield (5340 kg ha-1) and straw yield (6013 kg ha-1) over the untreated control. The results strongly emphasize that endophytic bacteria (EMP-5) could be efficiently used for management of bacterial leaf blight.